Emotion-focused care for patients with dementia: defining distress and responsive care from hospital staff - Petty, Stephanie (2020)
Hospital care for patients with dementia needs to improve because of concern for patient wellbeing and hospital resources. When patients are distressed, care is particularly challenging. This thesis sets out definitions of emotional distress and emotion-focused care for hospital patients with dementia. Drawing directly upon the contributions of patients and ward staff, the thesis proposes solutions for improving care for patients in real-life hospital settings.